ANALISIS HUBUNGAN KUALITAS PELAYANAN PUBLIK RAWAT JALAN DENGAN KEPUASAN PASIEN BPJS (STUDI KASUS DI RSUD UNGARAN KABUPATEN SEMARANG) - Mela Nofitri; Ayun Sriatmi; Eka Yunila Fatmasari (Jurnal Kesehatan Masyarakat (Undip), 2020)
One form of public service is health services. Ungaran Regional General Hospital is one of the public service providers that aims to provide quality services for the community. Every year Ungaran Regional Hospital always experiences an increase in the number of patients, especially BPJS patients, namely in 2014-2016 as many as 64.8%. The increasing number of outpatient visits is not proportional to the satisfaction obtained by patients. This research is a survey research with quantitative methods. The population in the study were all BPJS outpatient polyclinic at Ungaran District Hospital with a sample size of 100 patients representing each sub-poly outpatient service. The results showed that there was a relationship between the dimensions of outpatient public service quality and patient satisfaction at Ungaran Regional Public Hospital BPJS, namely the tangible dimension of service with a p-value of 0.001 and a correlation of 0.320, the reliability dimension with a p-value of 0.004 and a correlation of 0.201, the responsiveness dimension with the p-value 0.013 and correlation 0.247, assurance dimension with p-value 0,000 and correlation 0.508, empathy dimension with p-value 0,000 with correlation 0.460.Based on the results of the study, the researcher recommends optimizing online registration services that are separated between general patients and BPJS patients, providing adequate seat facilities in the waiting room for registration, creating a service flow scheme that is easy for patients to understand and placing in the registration section, placing suggestion boxes in strategic places and easy to reach, and improving communicative services between officers and patients.